ENVIRONMENTAL PRACTICES AS AN INSTRUMENT OF INCLUSION FOR PEOPLE WITH DISABILITIES - Tavares, Vanda Fernandes; Dias, Victor Henrique Rodrigues; de Souza, Dandara Lima; Moy, Paulo André da Silva; da Silva Júnior, Mário Lopes; Teixeira, Orivan Maria Marques; de Melo, Vânia Silva (Seven Editora, 2024)
The study evaluates the contribution of environmental education practices in the lives of people with intellectual disabilities served at APAE - Barcarena through environmental education workshops that are part of the project "Ecoefficient Education: School, Society, Environment and Sustainability", developed through a partnership between the Federal Rural University of the Amazon (UFRA), through the Institute of Agrarian Sciences (ICA) and the Amazon Center for Accessibility,  Inclusion and Technology (ACESSAR), and the Company Navegações Unidas Tapajós (Unitapajós). The great challenge of humanity is to reduce the predatory action of man on natural resources and environmental education practices are important tools in the process of awareness and inclusion of people with intellectual disabilities to achieve harmony between man and nature with mutual benefits. In this context, a qualitative research was carried out through a bibliographic survey and application of a questionnaire with questions related to the theme. The results show that the use of environmental education practices to promote socio-educational inclusion proved to be an important tool in the inclusion of people with intellectual disabilities, providing the development of motor coordination, social inclusion and improvements in daily practices and healthy eating.DOI: https://doi.org/10.56238/sevened2024.037-113